Development of free neuromasts in larvae of cyprinid fish - Mukai, Yukinori; Kobayashi, Hiroshi (Kinki university, 2004)
Development of free neuromasts of two species cycprinid fishes was examined Distribution of free neuromasts and physiological sensitivity were examined.